Senderismo y el ecoturismo en el cerro El Muerto, Parroquia el Morro, cantón Guayaquil - Peralta Chafla, Julia Susana (2022)
Hiking is a tourist activity that is found in ecotourism, which seeks sustainability between economic, social and environmental activities, through ecological activities that contribute to the learning of tourists about the attention of nature and encourage their paste in the practice; Therefore, in this case, it is ideal to carry out this research, because the parish “El Morro” and “Cheerful Field” sector, the sharp communities seeking tourism development. In addition, they have as objective the conservation and protection of natural resources that Hill “Elad” has, which is a place that has a large amount and variety of vegetation, beautiful mountainous elevations and excellent landscapes for photos and enjoy the family. And friends an army emotion in a natural envelope. The present research work aims to develop some proposals that help improve tourism and achieve a tourism sector with the help of nearby communities, which will be external beneficiaries of the production and implementation of the project. The general idea is based on containing tourism from all areas of induction to the natural environment, through the tourist link, which offers each place of connection, satisfying the needs of tubists.